Análise de critérios e fatores de sucesso em projetos de engenharia, suprimentos e construção (EPC) offshore - Bahia, Fabio Dias (2009)
The projects in the petroleum industry (oil, gas and derivatives) are characterized by their technical complexity and management. These projects are planned, designed, and executed by large, distributed, multi-disciplinary teams that strive to implement innovative solutions that will allow exploring and producing oil and gas from deep water fields (Offshore). In this scenario, it is evident the importance of new knowledge leading to increased management competence of the organizations that are involved in Engineering, Procurement and Acquisition (EPC) projects. Based on a literature review related to EPC Projects , Offshore Projects and Project Success , and a questionnaire responded by 37 experienced professionals, working for 24 different organizations of the sector, it was possible to identify the main objectives or success criteria (Cost, Time, Quality, Scope, Customer Satisfaction, Security, Team Satisfaction and Shareholder Satisfaction) as well as the named Hypercritical Success Factors (Competent Project Manager, Planning, Qualified Project Team and Realistic Budget), among other Critical Success Factors. The understanding of the relative importance of the critical success factors to each performance objective is another key element in this research. It is important to emphasize that this dissertation discuss EPC Offshore Project success from the EPC contractors (named in Brazil as EPCistas ) point of view